Penerapan Lean Manufacturing Guna Mengurangi Waste dengan Metode Value Stream Mapping dan Waste Assessment Model Pada Home Industry Konveksi Warsito - Rieska Ernawati; Nuzulia Khoiriyah; Nova Miranda; Nurul Istikomah; Bunga Zahrotun Na’imah; Fathur Eko Prasetyo Aditya (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2024)
One of the home industry conventions warsito in the Pati area produces clothing products like pyjamas. This home industry is run by individuals or families on a small scale. Convex home industries often face the challenge of managing efficient production processes and meeting consumer expectations. Faced with such challenges, they often face problems of waste in the production process, such as excessive inventory, waiting times, unnecessary movements, and inefficient processes. Therefore, to eliminate such waste, the concept of lean manufacturing is needed. This research discusses waste reduction using the Value Stream Mapping (VSM) and Waste Assessment Model (WAM) methods. With this method, non-value added identification is produced through the process flow and the relationship of waste to each other. There are 2 largest wastes, namely waste defect and waste motion, which then require improvement proposals by analyzing the causes/root causes of the waste using a fishbone diagram. From this method, waste defect with a percentage of 20.452% and waste motion with a percentage of 16.16%. The improvement proposal for dealing with waste defects is to apply the 5s principle, group materials by type and color, schedule machine maintenance. At waste motion it is recommended to set the work position, use aids such as jig, quality control of materials, set a sewing machine calibration schedule.